Flouting Maxim Analysis in ‘The Wonderful Story of Henry Sugar’ Movie - Alhafidz, Nabil; Silaen, George; Zannah, Khoirunnisa ul; Natsir, Muhammad (Lembaga Riset Mutiara Akbar, 2024)
The aim of this research is to identify maxim flouting in the film